Intelligent Carbon Metering and Settlement Method of New Power System Based on Blockchain Technology - Ruxin Wen; Wen Tian; Huiying Liu; Wenjuan Lin; Xizhong Zhou; Xuerong Li (Energies)
Blockchain technology is an important technical basis for ensuring carbon trading and plays a fundamental role in maintaining fairness in the carbon trading market. This paper proposes a carbon emission metering and settlement method and a system based on blockchain technology which creates the digital identity of electric meters and stores it in the blockchain. Verifiable credentials are generated based on the digital identity, energy data, and time stamp. The system records the energy data read by the verified meter to the blockchain cloud platform for carbon emission statistics. In the payment and settlement stage, through application of the blockchain and its combination with a digital payment wallet, the regional energy network consumption settlement value is generated according to the regional power supply and electricity consumption, and the settlement value is used as the benchmark to measure the carbon emissions in the region. Through the data analysis of practical application cases in an industrial park in China, this study concludes that the carbon emission statistical settlement method based on blockchain technology solves the problems of untrustworthiness, unreliability, and inconsistency in the statistical and settlement methods during the statistical settlement of electric energy statistics and energy consumption carbon emissions.